Reassessing the Evolutionary History of the 17q21 Inversion Polymorphism. (11th November 2015) - Alves, Joao M.; Lima, Ana C.; Pais, Isa A.; Amir, Nadir; Celestino, Ricardo; Piras, Giovanna; Monne, Maria; Comas, David; Heutink, Peter; Chikhi, Lounès; Amorim, António; Lopes, Alexandra M.
Abstract: A polymorphic inversion that lies on chromosome 17q21 comprises two major haplotype families (H1 and H2) that not only differ in orientation but also in copy-number. Although the processes driving the spread of the inversion-associated lineage (H2) in humans remain unclear, a selective advantage has been proposed for one of its subtypes. Here, we genotyped a large panel of individuals from previously overlooked populations using a custom array with a unique panel of H2-specific single nucleotide polymorphisms and found a patchy distribution of H2 haplotypes in Africa, with North Africans displaying a higher frequency of inverted subtypes, when compared with Sub-Saharan groups. Interestingly, North African H2s were found to be closer to "non-African" chromosomes further supporting that these populations may have diverged more recently from groups outside Africa. Our results uncovered higher diversity within the H2 family than previously described, weakening the hypothesis of a strong selective sweep on all inverted chromosomes and suggesting a rather complex evolutionary history at this locus.